Impact of indoor environmental quality (IEQ) and innovation (IN) features on residential property price in Malaysia: a review - Megat Abd Rahman, Megat Mohamed Ghazali (2015)
The purpose of this paper is to review the broad literature regarding the impacts of indoor environmental quality (IEQ) and innovation (IN) for residential building property and its implication towards property price and rental. The early hypothesis of this paper anticipate that innovation (IN) and indoor environmetal quality (IEQ) features will indirectly increase residential property market price and rental in spite of the lack of comparative financial data. Research limitations/implications – This research will focus on multi-storey residential buildings. They are condominium, apartment or service apartment with IN and IEQ features based on Green Building Index (GBI) assessment criteria. In this research, IN and IEQ features will be defined according to the description of Green Building Index (GBI) Assessment Criteria for New Residential Construction (RNC). Originality/value – To the best of researcher's knowledge, in the context of Malaysia there is no single study emphasized on the significant role of IEQ and IN criteria especially its interrelation with property price and value. From this paper, it is hope that the positive impacts of these features will encourage building owners, developers and other main development actors to put these criteria into the same consideration as other criteria in GBI as one of the way to compensate the impact of the building towards economic, environment and social.